Ritual Tuko Belai (Peletakan Tiang Raja) di Desa Darawa Kecamatan Kaledupa Selatan Kabupaten Wakatobi - Noor Astikalmira; La Ode Dirman; Nurtikawati Nurtikawati (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
The study was conducted in the village of Darawa, South Kaledupa District, Wakatobi Regency with the aim of describing the process of performing the tuko belai ritual (placement of the king's pole) in the village of Darawa, South Kaledupa District, Wakatobi Regency and explaining the symbolic meanings contained in it. The research method used was qualitative with the determination of informants using snowball sampling, then data was obtained through observation, interviews, and communication and then analyzed. The results of this research showed that the process of performing the tuko belai ritual consists of the initial stage, implementation, and final stage. The tuko belai ritual has the meaning of avoiding evil spirits or supernatural creatures that can disturb the life of the inhabitants of the house later, as a repeller of misfortune (Bala'a), a prayer for safety (doa selamat), blessed with health, blessed with prosperity, and given a long life.